The gut-heart axis: unveiling the roles of gut microbiota in cardiovascular diseases - Zhang, Yuan; Wu, Huimin; Jin, Mu; Feng, Guirong; Wang, Sheng (Frontiers in Cardiovascular Medicine, 2025)
The gut microbiome refers to the collective genomes of the approximately 1,000–1,150 microbial species found in the human gut, called the gut microbiota. Changing the gut microbiota composition has been shown to affect cardiovascular health significantly. Numerous studies have demonstrated the part that gut microbiota and its metabolites play in the development and course of several illnesses, including colon cancer, heart failure, stroke, hypertension, and inflammatory bowel disease. With cardiovascular diseases responsible for more than 31% of all fatalities globally, conditions like hypertension, atherosclerosis, and heart failure are serious global health issues. Developing preventive measures to fight cardiovascular diseases requires understanding how the gut microbiota interacts with the cardiovascular system. Understanding the distinctive gut microbiota linked to cardiovascular diseases has been made possible by microbial sequencing analysis. The gut microbiota and cardiovascular diseases are closely related, and more profound knowledge of this association may result in treatment strategies and broad guidelines for enhancing cardiovascular health through gut microbiome modification. This review summarizes the role of gut microbiota in cardiovascular diseases, highlighting their influence on disease progression and potential therapeutic implications.